The Impact of Auditing Practices on Service Delivery in the District Assemblies of Ghana - Scott, George Kojo (New Innovations in Economics, Business and Management Vol. 7, 2022)
Auditing practices is one of the key sub-components of public financial management primarily concerned with examining and ascertaining whether public resources were used for the purposes they were budgeted for in line with the set regulations. The objective of this research was to determine the impact of auditing as practiced in Ghana’s district assemblies (DAs) on service delivery. The study used a mixed methods research design to collect qualitative and quantitative data through questionnaires, interviews, focus group discussions, and document analysis. Thirty-four districts out of 170 that existed in 2008 were sampled. The study gathered information from 612 DA officials, 1020 citizens, 28 key informants and 20 participants in focus group discussions. Quantitative data was measured by using scaled-items, and analysed using descriptive statistics and multiple regression. For qualitative data, the researcher used thematic summary analysis. According to the findings, citizens rated service delivery poorly, whereas district assembly officials rated service delivery as satisfactory. The research also found that auditing practices had a positive but insignificant effect on service delivery. The study recommends that district assemblies and authorities work hard to integrate and improve innovative communication tools such as websites, Facebook, Twitter, and WhatsApp to supplement the interaction activities of auditors, those who implement audit findings, and other stakeholders. DAs should increase the current capacity of audit staff. DAs should also work towards strengthening the role of sector audit implementation committees, ensure strict enforcement of audit reports, and enforce sanctions of officers culpable of malpractices.